An Intertropical Convergence Zone shift controlled the terrestrial material supply on the Ninetyeast Ridge - X. Xu; J. Liu; Y. Huang; L. Zhang; L. Yi; S. Liu; Y. Yang; L. Cao; L. Tan (Climate of the Past, 2022)
Among various climate drivers, direct evidence for the Intertropical Convergence Zone (ITCZ) control of sediment supply on the millennial scale is lacking, and the changes in ITCZ migration demonstrated in paleoclimate records need to be better investigated. Here, we use clay minerals and Sr–Nd isotopes obtained from a gravity core on the Ninetyeast Ridge to track the corresponding source variations and analyze the relationship between terrestrial material supply and climatic changes. On the glacial–interglacial scale, chemical weathering weakened during the North Atlantic cold-climate periods and falling sea level hindered the transport of smectite into the study area due to the exposure of Andaman and Nicobar Islands. However, the influence of the South Asian monsoon on the sediment supply was not obvious on the millennial scale. We suggest that the north–south migration of the ITCZ controlled the rainfall in Myanmar and further directly determined the supply of clay minerals on the millennium scale because the transport of smectite was highly connected with the ITCZ location; thus, the regional shift of the ITCZ induced an abnormal increase in the smectite percentage during the late Last Glacial Maximum (LGM) in our records. The smectite percentage in the studied core is similar to distinct ITCZ records but different in some periods, revealing that regional changes in the ITCZ were significantly obvious, the ITCZ is not a simple north–south displacement, and closer connections occurred between the Northern–Southern Hemisphere in the eastern Indian Ocean during the late LGM.